(untitled) (mathematica didactica, 2008)
The title may confuse. He who centralizes goes to the midth; who optimizes looks at the edges. But there are interesting, mutually elucidating relations between these two activities. We indicate them for 2 data and extend them for 3 and 4 data. The next step is a generalization on n data. Finally we give a didactical comment about aims and scope of our unit.